CLINICAL AND EPIDEMIOLOGICAL CHARACTERISTICS OF SEROUS MENINGITIS IN ADULTS IN THE KHMELNYTSKYI REGION (PODILSK REGION, UKRAINE): ELEVEN-YEAR EPIDEMIOLOGICAL STUDY - Pypa, L.V.; Svistilnik, R.V.; Lysytsia, Yu.N.; Yuzvyshyna, O.V.; Polishchuk, O.V. (World of Medicine and Biology, 2018)
Object. The aim of the work was analyzing the etiological structure, epidemiological features, socio-demographic profiles and the nature of the development of complications from the central nervous system (CNS) in serous meningitis in adults of the Khmelnytskyi region for the period of 2007-2017.Materials and methods. We were analyzing 193 cases of serous meningitis in adults from 2007 to 2017 of which 103 (53,4%) were men and 90 (46,6%) were women. The etiology of the disease was determined by studying the liquor by PCR method. Complications were determined on base of the clinical picture and the method of MRI. The study used an analytical method. Results. Analyzing the dynamics of morbidity in the SM in adults, it can be noted its relatively stationary nature. Serous meningitis occurs in adults during all seasons however the lowest incidence was observed in the winter (17,6%) and spring (19,7%) periods, increasing in the summer (29,0%) reaching the maximum in the autumn period (33,7%). According to age categories the incidence of SM was distributed as follows: aged 18-39 years old, 139 people (72,0%), 40 persons to 59 years old - 40 (20,7%) and over the age of 60 - 14 (7,3%). The average age of SM patients was 34,4 ± 14,6 years that is mostly young and able-bodied people are ill.According to the data the number of males who were suffering from SM was 103 (53,4%) while females were 90 (46,6%) which corresponded to the ratio of males to females 1,1:1.The clinical picture in most cases was characterized by severe course (78,2%) and in 21,8% of cases, the course of moderate severity. In the overwhelming majority of the diseases meningitis (72,0%) was over, whereas meningoencephalitis was diagnosed in 28,0% of cases. In 100% of the cases the disease began with fever, headache (94,3%), vomiting (80,4%), seizures (2,6%). The meningeal syndrome was detected in 97,9% of patients. The diagnosis of SM was based on the study of liquor. In the general average, the cytosis was 422,5 ± 291,8 cells with predominance of lymphocytes and the mean protein level in the liquor was – 0,80 ± 0,28 g/l.The etiological factor of SM was established in 21 (10,9%) patients. In general the main causative agent among the SM in adults is herpes viruses which were determined in 9 (42,8%) cases HSV-1/2 (4 patients) and VZV (4 patients) and HSV-6 (1 patient) were among the herpes viruses. The second ranked place occupied enterovirus which was determined in 6 (28,6%) patients, the third place was occupied by the pathogen of tuberculosis, which was detected in 4 (19,0%) patients. In one case the pathogens of iersiniosis and leptospirosis were determined (in 4,7% of cases).In our observation, 65 (33,7%) patients experienced complications of the disease, most of which needed appropriate treatment. Most often brain edema was observed in 33 patients (50,7%), 10 cases developed convulsive seizures (15,4%), and 8 patients (12,3%) experienced paresis of extremities. Conclusions. Mostly young people are ill (72% in the age structure), the average age is 34,4 ± 14,6 years in the ratio of men to women 1.1:1.The main pathogens of serous meningitis were herpes virus (42,8%), enterovirus (28,6%) and mycobacterium tuberculosis (19%). In 33,7% of patients there were complications from the central nervous system. In our study the prevalence of SM among adults in the Khmelnytskyi region was 1,35 per 100,000 adult population with a male to female ratio of 1,1:1.
Keywords: serous meningitis; epidemiology; etiology; adults